The Influence of Samsung Smartphone Quality on Consumer Purchase Decisions - Teuku, Teuku Reza Kurniawan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
The purpose of this study was to determine the effect of product quality on purchasing decisions for Samsung smartphones. The research method used is quantitative research. The sampling technique used incidental sampling, with samples taken using the Slovin formula as many as 89 people. Findings Based on the partial test (test) it is known that there is a significant and positive influence between the product quality variables on purchasing decisions. It was also found that product quality contributed 51.6% to purchasing decisions while 48.4% was determined by other variables not included in this study.